Infinitely Many Standing Waves for the Nonlinear Chern-Simons-Schrödinger Equations - Jinmyoung Seok (Advances in Mathematical Physics)
We prove the existence of infinitely many solutions of the nonlinear Chern-Simons-Schrödinger equations under a wide class of nonlinearities. This class includes the standard power-type nonlinearity with exponent p>4. This extends the previous result which covers the exponent p>6.